(untitled) (Fiep Bulletin - online, 2011)
The article aims to present a synthesis of the literature with reference to the studies made so far on the development of body image in female adolescents. We collect information from the data of completed surveys, which confirm the need to raise questions and reflections about the imposition of aesthetic standards for the body and the consequences in shaping the body image of adolescents. We note the concerns of the scientific community with the increasing dissatisfaction of the young with their bodies and the search at any cost to be within the culturally imposed standards. Research on the implications of school Physical Education was the central paradigm of Teacher Thinking.